Case report: Later onset of NRAS-mutant metastatic melanoma in a patient with a partially-excised giant congenital melanocytic nevus - Costa, Bruno Almeida; Zibara, Victor; Singh, Vasundhara; Hamid, Omid; Gandhi, Sonal; Moy, Andrea P.; Betof Warner, Allison S. (Frontiers in Medicine, 2022)
Despite recent advances in treatment and surveillance, metastatic melanoma still carries a poor prognosis. Large/giant congenital melanocytic nevi (CMNs) constitute a known risk factor for the condition, with the greatest risk for malignant transformation thought to be during childhood (median age at diagnosis of 3 years in a previous cohort). Herein, we present the case of a 30-year-old male who, after undergoing multiple excision/grafting procedures for a giant CMN as a child, was diagnosed with an NRAS-mutant, MDM2-amplified metastatic melanoma more than 20 years later. Response to ipilimumab/nivolumab immunotherapy, cisplatin/vinblastine/temozolomide chemotherapy, and nivolumab/relatlimab immunotherapy was poor. This case highlights the importance of lifetime monitoring with once-yearly dermatological examination (including lymph node palpation) in large/giant CMN patients, as well as the need for further clinical trials evaluating novel therapies for NRAS-mutant melanoma.